PROSPECT guideline for total hip arthroplasty: a systematic review and procedure‐specific postoperative pain management recommendations. (20th May 2021) - Anger, M.; Valovska, T.; Beloeil, H.; Lirk, P.; Joshi, G. P.; Van de Velde, M.; Raeder, J.; ,
Summary: The aim of this systematic review was to develop recommendations for the management of postoperative pain after primary elective total hip arthroplasty, updating the previous procedure‐specific postoperative pain management (PROSPECT) guidelines published in 2005 and updated in July 2010. Randomised controlled trials and meta‐analyses published between July 2010 and December 2019 assessing postoperative pain using analgesic, anaesthetic, surgical or other interventions were identified from MEDLINE, Embase and Cochrane databases. Five hundred and twenty studies were initially identified, of which 108 randomised trials and 21 meta‐analyses met the inclusion criteria. Peri‐operative interventions that improved postoperative pain include: paracetamol; cyclo‐oxygenase‐2‐selective inhibitors; non‐steroidal anti‐inflammatory drugs; and intravenous dexamethasone. In addition, peripheral nerve blocks (femoral nerve block; lumbar plexus block; fascia iliaca block), single‐shot local infiltration analgesia, intrathecal morphine and epidural analgesia also improved pain. Limited or inconsistent evidence was found for all other approaches evaluated. Surgical and anaesthetic techniques appear to have a minor impact on postoperative pain, and thus their choice should be based on criteria other than pain. In summary, the analgesic regimen for total hip arthroplasty should include pre‐operative or intra‐operative paracetamol and cyclo‐oxygenase‐2‐selective inhibitors or non‐steroidal anti‐inflammatory drugs, continued postoperatively with opioids used as rescue analgesics. In addition, intra‐operative intravenous dexamethasone 8–10 mg is recommended. Regional analgesic techniques such as fascia iliaca block or local infiltration analgesia are recommended, especially if there are contra‐indications to basic analgesics and/or in patients with high expected postoperative pain. Epidural analgesia, femoral nerve block, lumbar plexus block and gabapentinoid administration are not recommended as the adverse effects outweigh the benefits. Although intrathecal morphine 0.1 mg can be used, the PROSPECT group emphasises the risks and side‐effects associated with its use and provides evidence that adequate analgesia may be achieved with basic analgesics and regional techniques without intrathecal morphine. 요약: 이 체계적 문헌 고찰의 목적은 2005년에 출판되고 2010년 7월에 업데이트된 시술별로 특화 된 수 술 후 통 증 관 리 (PROSPECT)의 이전 지침을 업데이트하여 인공 고관절 전치 환술 후의 통증 관리에 대한 권고사항을 개발하는 것이었다. 진통제, 마취, 수술 또는 다른 중재를 사용하고 수술 후 통증을 평가한, 2010년 7월과 2019년 12월 사이에 출판된 무작위 대조 시험들과 메타분석들을 MEDLINE, Embase, Cochrane 데이 터베이스로부터 검색하였다. 일차적으로 520건의 연구가 확인 되었고, 그중 108건의 무작위 시험과 21건의 메타분석이 기준 을 충족하였다. 수술 후 통증을 개선한 주술기 중재들은 파라 세타몰(paracetamol), 사이클로옥시게나제‐2 (COX‐2) 선택 적 억제제, 비스테로이드성 소염제, 덱사메타손(dexametha‐ sone) 정맥 주입 등이 있다. 또한, 말초신경차단(대퇴신경차 단, 요추신경총차단, 장골근막차단), 일회성 국소침윤마취, 경 막내 모르핀과 경막외 진통제 투여도 통증을 개선시켰다. 이 외에 평가된 다른 모든 진통 방법들에 대해서는 증거가 불충 분하였다. 수술과 마취 방법들이 수술 후 통증에 미치는 영향 은 미미한 것으로 보이므로, 이들의 선택은 통증 이외 기준에 따라 이루어져야 한다. 요약하면, 인공 고관절 전치환술을 위 한 진통 요법은 수술 전 또는 수술 중 파라세타몰과 사이클로 옥시제나제‐2 선택적 억제제 또는 비스테로이드성 소염제를 포함해야 하며, 수술 후에는 이들의 지속적인 복용 및 구조 진통 요법으로 아편유사제 사용이 동반되어야 한다. 또한, 수 술 중 8‐10 mg의 덱사메타손 정맥 주사가 권장된다. 특히 기 본 진통제에 대한 금기사항이 있거나 수술 후 강한 통증이 예 상되는 환자들의 경우, 장골근막차단이나 국소침윤마취와 같 은 부위 진통 기술들이 권장된다. 경막외 진통제, 대퇴신경차 단, 요추신경총차단과 가바펜티노이드(gabapentinoid) 투여 는 부작용이 이점보다 크기 때문에 권장되지 않는다. 경막내 모르핀 0.1 mg이 사용될 수는 있지만, PROSPECT 그룹은 이 러한 사용과 관련된 위험과 부작용들을 강조하고, 경막내 모 르핀 없이도 기본적 진통제와 부위 진통 기법들로 충분한 진 통이 이루어질 수 있다는 증거를 제공한다.